2022
DOI: 10.21203/rs.3.rs-2160155/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal multi-omic changes in the transcriptome and proteome of peripheral blood cells after a 4 Gy total body radiation dose to Rhesus macaques

Abstract: Background: Non-human primates, such as Rhesus macaques, are a powerful model for studies of the cellular and physiological effects of radiation, development of radiation biodosimetry, and for understanding the impact of radiation on human health. Here, we study the effects of 4 Gy total body irradiation (TBI) at the molecular level out to 28 days and at the cytogenetic level out to 56 days after exposure. We combine the global transcriptomic and proteomic responses in peripheral whole blood to assess the impa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Based on data from historical accidents, Goans and colleagues [Goans et al, 1997;Goans et al, 2001] reported that the onset of lymphopenia in vivo is rapid and follows an approximate exponential decline within the first 24-48 h following gamma ray exposure. A rapid rise in neutrophil cell counts and decrease in lymphocyte levels in vivo has also been reported in the non-human primate model within 24 h after TBI [Farese et al, 2021;Ghandhi et al, 2023]. Hematology kinetics showed that with increasing time post-exposure, WBCs, neutrophils, lymphocytes, PLTs, and RBCs decreased, highlighting radiation-induced myelosuppression with pancytopenia.…”
Section: Discussionmentioning
confidence: 57%
“…Based on data from historical accidents, Goans and colleagues [Goans et al, 1997;Goans et al, 2001] reported that the onset of lymphopenia in vivo is rapid and follows an approximate exponential decline within the first 24-48 h following gamma ray exposure. A rapid rise in neutrophil cell counts and decrease in lymphocyte levels in vivo has also been reported in the non-human primate model within 24 h after TBI [Farese et al, 2021;Ghandhi et al, 2023]. Hematology kinetics showed that with increasing time post-exposure, WBCs, neutrophils, lymphocytes, PLTs, and RBCs decreased, highlighting radiation-induced myelosuppression with pancytopenia.…”
Section: Discussionmentioning
confidence: 57%
“…As an alternative method for radiation biodosimetry, additional methods such as γ-H2AX, 6,7 micronuclei, 5,8 microRNA, 9,10 lncRNA, 11,12 and protein [13][14][15] and gene expression signatures [16][17][18] in peripheral blood cells are being developed for this purpose. 19 Gene expression assays have been particularly promising, and typically measure the mRNA content in a certain simulated scenario with reference to normal expression levels.…”
Section: Introductionmentioning
confidence: 99%